Teaching of Biology Supported by Mathematical Models - Joanna Maciejewska; Janusz Uchmański (Studia Ecologiae et Bioethicae)
In the life sciences, the use of mathematical modelling and computer simulation methods has brought many benefits. This is the case, for example, in physics. Biology makes very little use of these methods. One of the reasons for this may be that the biology teaching process is conducted in such a way that it discourages young people with an interest in mathematics and computer science. We propose to support the process of teaching biology by introducing simple elements of mathematical modelling of ecological processes. In this work, we showed what benefits would be the application of the NetLogo program in teaching biology in secondary schools. NetLogo is a multi-agent programming language designed to simulate complex phenomena. It is intended for both research and education and is used in a wide variety of scientific disciplines. We used the NetLogo program to create a model of searching for food by ants. We have shown that teaching biology by building a computer model forces a deeper understanding of the problem we are working on and uses and develops the creative abilities of young people.